2008
DOI: 10.1038/oby.2007.73
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Intensity and Risk of Overweight and Adiposity in Children

Abstract: background: Physical activity recommendations for children focus on duration of activity and underemphasize intensity. objective: To evaluate the relationship between physical activity (intensity and duration) and the odds of being overweight, >20% body fat and >25% body fat. Methods and Procedures: Body fat, BMI and physical activity (accelerometry) were measured in children (n = 251) aged 8-10 years. Physical activity was quantified as time in moderate physical activity (MPA) and vigorous physical activity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
60
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 43 publications
(85 reference statements)
11
60
0
5
Order By: Relevance
“…Physical activity, especially moderate-to-vigorous physical activity, is associated with beneficial metabolic profiles 8,16) . In the present study, time spent on exercise was associated with lower risks of hypertension, dyslipidemia, and insulin resistance, as shown by simple regression analysis; however, multivariate regression analysis showed that participation in EC Data are expressed as the mean (standard deviation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity, especially moderate-to-vigorous physical activity, is associated with beneficial metabolic profiles 8,16) . In the present study, time spent on exercise was associated with lower risks of hypertension, dyslipidemia, and insulin resistance, as shown by simple regression analysis; however, multivariate regression analysis showed that participation in EC Data are expressed as the mean (standard deviation).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with a cluster of cardiovascular (CV) risk factors, including abdominal obesity, impaired glucose tolerance, hypertension, and dyslipidemia, which have collectively been termed metabolic syndrome in both children and adults 3,4) . It is well known that the development of CV risk factors, including obesity, is associated with adverse behavioral patterns, such as decreased physical activity [5][6][7][8] , increased sedentary lifestyle, in particular television (TV) watching [8][9][10][11] , and unhealthy dietary habits 5,[11][12][13][14][15][16] . Parental obesity is also strongly associated…”
mentioning
confidence: 99%
“…A series of studies was conducted using BMI as the reference variable to determine step-count cutoffs (Laurson et al, 2008;McCormack, Rutherford, Giles-Corti, Tudor-Locke, & Bull, 2011;Tudor-Locke et al, 2004), but BMI often misrepresents the weight problem of children due to its inability to account for maturation status and muscle mass (Nihiser et al, 2007). Duncan, Schofield, and Duncan (2007) improved upon the use of BMI by choosing body fat percentage as the criterion variable to select cutoffs, but neither BMI nor body fat are direct measures of physical activity behavior, and the correlation between body composition measures and physical activity behavior has generally been weak (Ribeiro et al, 2003;Wittmeier, Mollard, & Kriellaars, 2008). Several of these studies also determined step-count cutoffs by multiples of 1,000 steps (Duncan et al, 2007;McCormack et al, 2011;Rowlands & Eston, 2005;Tudor -Locke et al, 2004;Vincent & Pangrazi, 2002), which may significantly misrepresent the assessment of physical activity habits (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Aim of the present study is to further research the two parental food controlling practices pressure and restriction as possible risk factors for overweight, this time by determining their relationships with various possible risk factors for overweight, specifically: Snacking, skipping a breakfast meal, low fruit consumption, physical inactivity and much time spend on screen media (television or computer) (Berkey, Rockett, Gillman, Field, & Coditz, 2003;Blass, Anderson, Kirkorian, Pempek, & Koleini, 2006;Hancox, Milne, & Poulton, 2004;Lin & Morrison, 2002;Snoek, Van Strien, Janssens, & Engels, 2007;Wittmeier, Mollard, & Kriellaars, 2008).…”
mentioning
confidence: 99%